Prinsip Keadilan Prosedural Sebagai Landasan Pertimbangan Hakim Dalam Kasus Pencurian Ayam - Muhammad Alvian Yudistira Chandra Chaerudin; Ali Maskur; Arina Hukmu Adila (JURNAL USM LAW REVIEW, 2025)
This research aims to analyze the application of the principle of procedural justice as the basis for the judge's consideration in the case of chicken theft (Decision Number: 518/PID.B/2024/PN SMG). The background of the research is the urgency of protecting the rights of defendants in the criminal justice system, especially for perpetrators from weak economic groups. The method used is normative juridical with a qualitative approach through the study of decision documents and interviews with judges. The results showed that the judge concretely considered the rights of the defendant, including the right to self-defense, obtaining a fair trial, and upholding the investigation procedure in accordance with applicable law. Unlike previous studies that focused more on substantive justice, this research specifically explores aspects of procedural justice in minor cases with social impacts. The novelty of this research lies in the focus of analysis on the application of procedural justice in criminal cases involving defendants from economically vulnerable groups. The findings contribute to the strengthening of a fairer, more inclusive, and transparent justice system.   Penelitian ini bertujuan menganalisis penerapan prinsip keadilan prosedural sebagai dasar pertimbangan hakim dalam perkara pencurian ayam (Putusan Nomor: 518/PID.B/2024/PN SMG). Latar belakang penelitian adalah urgensi perlindungan hak-hak terdakwa dalam sistem peradilan pidana, terutama bagi pelaku dari kalangan ekonomi lemah. Metode yang digunakan adalah yuridis normatif dengan pendekatan kualitatif melalui studi dokumen putusan dan wawancara dengan hakim. Hasil penelitian menunjukkan bahwa hakim mempertimbangkan secara konkret hak terdakwa, termasuk hak untuk membela diri, memperoleh peradilan yang adil, serta penegakan prosedur penyidikan sesuai hukum yang berlaku. Berbeda dengan studi sebelumnya yang lebih menitikberatkan pada keadilan substantif, penelitian ini secara khusus mengupas aspek keadilan prosedural dalam perkara ringan namun berdampak sosial. Kebaruan penelitian ini terletak pada fokus analisis terhadap penerapan keadilan prosedural dalam kasus pidana yang melibatkan terdakwa dari kelompok rentan secara ekonomi. Temuan ini memberikan kontribusi terhadap penguatan sistem peradilan yang lebih adil, inklusif, dan transparan.